The Community Participation in Tourism Sustainability and Tourist Satisfaction - Sari Lestari Zainal Ridho; Paisal Paisal; Dina Mellita; Muhammad Taufik Roseno (Jurnal Internasional Ilmu Pengetahuan Terapan bidang Pariwisata dan Events, 2021)
Purpose: The purpose of this study was to evaluate the role of community in economic sustainability towards post-visit behavior to cultural tourism destinations in the city of Palembang. Research methods: This research is a quantitative study, which examines the relationship between the variables of the role of community, in this case, the community, in the economy sustainability of tourism and several other variables, which is the role of the community in ecological, social, cultural sustainability toward post-visit behavior, in the form of tourist satisfaction. The technique analysis used was multiple regression analysis techniques and the data of this study were collected through a survey in 2019, using a questionnaire of 107 respondents who were tourists who had visited one of the cultural tourism destinations in Palembang. Result and Discussion: The results of this study indicate that the role or participation of community in the sustainability of tourism has a positive and significant effect on visitor or tourist satisfaction Conclusion: the community participation in tourism sustainability is significantly important in order to create tourist satisfaction; hence it’s important to focus on community empowerment.